ASSESSMENT OF KNOWLEDGE AND PRACTICES MENSTRUAL HYGIENE MANAGEMENT AMONG ADOLESCENT SCHOOL GIRLS - Manzoor, Dr. Tayyeba; Azam, Dr. Naila; Pervaiz, Dr. Farrah (Pakistan Armed Forces Medical Journal, 2019)
Background: Adolescent girls constitute about 1/5th of total female population worldwide. During menstruation,poor hygienic practices leads to multiple reproductive tract infections which have now become a silent epidemic. Worldwide approximately 10% of the women are exposed to genital infections including UTIs and bacterial vaginosis annually. In Pakistan, poor menstrual hygiene management (MHM) has been linked to negative consequences. Objective: To determine the knowledge, practices, and availability of Menstrual Hygiene Management facilities in girls’ schools and formulate recommendations for policy makers/reproductive health programmers. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Armed Forces Post Graduate Medical Institute from April 2018 to December 2018 Material and Methods: Sample size was 416 adolescent school girls. Universal sampling was used to include female teachers of selected schools. Validated structured questionnaire was adapted for data collection. Chi square test was used to present the results. Results: Only 3.8% of the respondents in public and private schools have good knowledge regarding MHM. Majority of the students knew about menstruation before attaining menarche and mother was common source of information. Good practices were reported among 33.7% in public and 48.1% in private schools. Over 50% of the girls used cloth during menstruation. Significant association was found between good practices and educational (p-value 0.001) and occupational (p-value 0.007) status of mother, educational (p-value 0.007) and occupational (pvalue 0.009) status of father, regular pocket money from parents (p-value 0.005) and monthly income of the family (p-value 0.003). Educational and occupational status of mother, occupational status of father revealed association with good knowledge of MHM (p-value 0.001). Water for hand washing, toilets, dignity kits were available in both schools. And soap was available only in public schools. Dustbins for disposal of absorptive material was missing in both schools. Conclusion: Inadequate knowledge and poor practices of MHM are key impediments to girl’s education and personal development.